Lembaga Keuangan Mikro Syariah sebagai upaya Pemberdayaan Masyarakat - Yuli, Sri Budi Cantika (Universitas Brawijaya, Indonesia, 2008)
Society empowerment through Sharia Micro Finance Institution is perceived as a strategic effort. This is due to the clasical problems confront by Micro Business Entity. One of them is capital requiremeni, not to mention off course other problems such as: managerial aspect and lower motivation to have forward looking orientation in developing their business. Nevertheless this aspect required integrative and ceaseless effort to support the success of economic society empowermeni. Sharia Micro Finance Institution is one of the Micro Economic entity that is most suitable to nurture the economic society empowerment. Due to the Sharia economic principle in its operation which would enable the nurturing of micro economic business entity, especially as a target of dakwah and not only for capital inducement but more likely on the monitoring and evaluation on the success of the entity which is also the responsibility of Sharia Micro Finance Institution. This is the requirement to maintain the continuity of Financial institution, hindering the failure of funding, and also as social mission carried out by Sharia Micro Finance Institution as an effort to established society empowerment.